2010
DOI: 10.4049/jimmunol.1000195
|View full text |Cite
|
Sign up to set email alerts
|

A Notch Ligand, Delta-Like 1 Functions As an Adhesion Molecule for Mast Cells

Abstract: Mast cells (MCs) accumulate in chronic inflammatory sites; however, it is not clear which adhesion molecules are involved in this process. Recently, the expression of Notch ligands was reported to be upregulated in inflammatory sites. Although Notch receptors are known as signaling molecules that can activate integrins, their contributions to the adhesion of MCs have not been studied. In this study, we demonstrated that mouse MCs efficiently adhered to stromal cells forced to express a Notch ligand, Delta-like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 68 publications
1
34
0
Order By: Relevance
“…6). It has been previously reported that NOTCH-ligand interactions affected cell-cell contacts and adhesion in cardiovascular abnormalities (28) and chronic inflammation (29). Similarly, NOTCH signaling activation was dispensable in their findings.…”
Section: Discussionmentioning
confidence: 71%
“…6). It has been previously reported that NOTCH-ligand interactions affected cell-cell contacts and adhesion in cardiovascular abnormalities (28) and chronic inflammation (29). Similarly, NOTCH signaling activation was dispensable in their findings.…”
Section: Discussionmentioning
confidence: 71%
“…Additionally, RBP-J-deficient DCs showed diminished expression of CXCR4 and CCR7, critical chemokine receptors for DC differentiation and migration (39,49). Also, Notch molecules have been involved in other important functions such as the communication between DCs and NK cells (50), protection from apoptosis (51), and adhesion between mast cells and stromal cells (52).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, because DLL1 participates in fat metabolism, 26,27 it could be used as an indicator of M. tuberculosis infection. To explore DLL1 as a potential new tool for the diagnosis of TBM, the present study adopted an enzyme-linked immunosorbent assay (ELISA) for the quantitative measurement of DLL1 in CSF and serum samples from different patient groups: those with infection of the CNS, those with intracranial metastatic tumour and those with no diagnosis.…”
Section: Introductionmentioning
confidence: 99%